Contemporary Comparison of Open to Robotic Prostatectomy at a Veteran's Affairs Hospital. Issue 5 (7th December 2018) - Desai, Anuj; Hudnall, Matthew; Weiner, Adam B; Patel, Mehul; Cohen, Jason; Gogana, Pooja; Sharifi, Roohallah; Meeks, Joshua J
Abstract: Introduction: Among veterans, prostate cancer is the most common malignancy and has a higher incidence compared to the rest of the nation. No study has compared the effectiveness of Robotic-assisted-laparoscopic radical prostatectomy (RALP) vs. open radical prostatectomy (ORP) in the Veteran's Affairs (VA) hospital setting during the adoption of RALP. Methods: Institutional Review Board approval was obtained. Retrospective review was completed on Veterans with prostate cancer who underwent ORP or RALP from March 2011 to January 2017 during the introduction of RALP at one VA hospital. Perioperative and functional outcomes between ORP and RALP were compared as well as between the initial 50 and final 53 RALPs. Results: Among 91 ORPs and 153 RALPs, RALP had significant reductions in blood transfusions [2(1.3%) vs. 44(40%), p < 0.001], length of stay [2 days(1–2) vs. 3 days(2–4), p < 0.001], Clavien grade >2 complications [1(0.7%) vs. 20 (22.0%), p < 0.001], urine leak [2(1.3%) vs. 11 (12.1%), p < 0.001], and ICU readmissions [0(0%) vs. 3(3.3%), p < 0.001]. There were no significant differences in positive margin status or functional outcomes. Compared to the first 50 cases, the last 53 RALPs demonstrated a shorter operative time (349 vs. 292 min, p < 0.001), lower EBL (300 vs. 150 mL, p < 0.001), more frequent 1-day length of stay (34% vs. 60%, p = 0.02), and fewer composite adverse events (82% vs. 51%, p = 0.004). Operative time for the final 53 RALPs (292 minutes) was shorter than that of ORP (325 minutes, p = 0.013). Conclusions: During the introduction of RALP at one VA hospital, RALP was associated with several improved parameters compared to ORP and similar operative times were noted after the first 100 cases of RALPs. RALP is safe to introduce in a VA setting without compromising outcomes.